Outcomes following Laminoplasty or Laminectomy and Fusion in Patients with Myelopathy Caused by Ossification of the Posterior Longitudinal Ligament: A Systematic Review. (November 2016) - Singhatanadgige, Weerasak; Limthongkul, Worawat; Valone, Frank; Yingsakmongkol, Wicharn; Riew, K. Daniel
Study Design: Systematic review. Objective: To compare laminoplasty versus laminectomy and fusion in patients with cervical myelopathy caused by OPLL. Methods: A systematic review was conducted using PubMed/Medline, Cochrane database, and Google scholar of articles. Only comparative studies in humans were included. Studies involving cervical trauma/fracture, infection, and tumor were excluded. Results: Of 157 citations initially analyzed, 4 studies ultimately met our inclusion criteria: one class of evidence (CoE) II prospective cohort study and three CoE III retrospective cohort studies. The prospective cohort study found no significant difference between laminoplasty and laminectomy and fusion in the recovery rate from myelopathy. One CoE III retrospective cohort study reported a significantly higher recovery rate following laminoplasty. Another CoE III retrospective cohort study reported a significantly higher recovery rate in the laminectomy and fusion group. One CoE II prospective cohort study and one CoE III retrospective cohort study found no significant difference in pain improvement between patients treated with laminoplasty versus patients treated with laminectomy and fusion. All four studies reported a higher incidence of C5 palsy following laminectomy and fusion than laminoplasty. One CoE II prospective cohort and one CoE III retrospective cohort reported that there was no significant difference in axial neck pain between the two procedures. One CoE III retrospective cohort study suggested that there was no significant difference between groups in OPLL progression. Conclusion: Data from four comparative studies was not sufficient to support the superiority of laminoplasty or laminectomy and fusion in treating cervical myelopathy caused by OPLL.